Prognostic significance of lymph node ratio in esophageal squamous cell carcinoma: insights from the South Asian population - Qureshi, Sajida; Abbasi, Waqas Ahmad; Jalil, Hira Abdul; Mughal, Saba; Quraishy, Muhammad Saeed (Frontiers in Oncology, 2025)
BackgroundEsophageal cancer (EC) is a significant health concern in South Asia, yet data on prognostic factors, such as lymph node ratio (LNR), in this region is limited. This study aims to assess the prognostic significance of LNR in esophageal squamous cell carcinoma (ESCC) patients undergoing concurrent neoadjuvant therapy followed by minimally invasive esophagectomy (MIE).MethodsThis retrospective study analyzed the clinical data of ESCC patients who underwent concurrent neoadjuvant therapy followed by MIE at Dr. Ruth K. M. Pfau Civil Hospital from 2019 to 2023. Lymph node ratios were derived and patients were categorized into three groups: LNR 0, LNR low (≤ 0.1), and LNR high (>0.1). Patient characteristics were compared along with lymph node groups, and survival outcomes were analyzed using the Kruskal Wallis and Chi-square/Fisher exact test, Pearson correlation, Kaplan-Meier (KM) estimates, and Cox regression models.ResultsAmong the 47 patients, 15 (31.9%) deaths were observed. Patients with a high LNR had a higher mortality rate (70%) compared to those with a low LNR (41.7%) and 0 LNR (12%) (p = 0.002). Additionally, patients with a high LNR (>0.1) were associated with poorer overall survival (OS) (30.0% vs. 58.3% vs. 88.0%, p < 0.001). A significant correlation was also observed between LNR and the number of metastatic lymph nodes (correlation coefficient = 0.928, p < 0.001).ConclusionOur findings demonstrate that high LNR emerged as an independent prognostic factor in ESCC patients undergoing concurrent neoadjuvant therapy followed by MIE.